2008
DOI: 10.1538/expanim.57.11
|View full text |Cite
|
Sign up to set email alerts
|

Licorice Extract Does Not Impair the Male Reproductive Function of Rats

Abstract: Abstract:The effect of water extract of licorice (Glycyrrhiza uralensis)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
(65 reference statements)
2
11
1
Order By: Relevance
“…Table (6) revels that the effect of the oral administration of licorice root extract at 15 mg/kg/day does not result statistically a significant differences in serum hormone levels of progesterone and testosterone and estradiol levels, (P>5.50) in the treated group as compared with the control group. The present results of effect of licorice root extract on testosterone hormone was in agreement with that illustrated in ref [86], as it has been reported that serum testosterone level tended to decrease without statistically significant difference between the control (mean 5.81 ng/ml) and treated (mean 5.65-5.66 ng/ml) rats, following 0 weeks treatment with licorice at high dose (1555 mg/Kg) group leading to reduction value of testosterone and did not show any abnormal signs. It was suggested that no observed adverse effect level of licorice extract at 055,1555 and at higher than 1555 mg/kg, the upper limit dose in the repeated dose toxicity protocol recommended in toxicity and that long term exposure to licorice might not cause profound adverse effects [86].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Table (6) revels that the effect of the oral administration of licorice root extract at 15 mg/kg/day does not result statistically a significant differences in serum hormone levels of progesterone and testosterone and estradiol levels, (P>5.50) in the treated group as compared with the control group. The present results of effect of licorice root extract on testosterone hormone was in agreement with that illustrated in ref [86], as it has been reported that serum testosterone level tended to decrease without statistically significant difference between the control (mean 5.81 ng/ml) and treated (mean 5.65-5.66 ng/ml) rats, following 0 weeks treatment with licorice at high dose (1555 mg/Kg) group leading to reduction value of testosterone and did not show any abnormal signs. It was suggested that no observed adverse effect level of licorice extract at 055,1555 and at higher than 1555 mg/kg, the upper limit dose in the repeated dose toxicity protocol recommended in toxicity and that long term exposure to licorice might not cause profound adverse effects [86].…”
Section: Resultssupporting
confidence: 93%
“…The present results of effect of licorice root extract on testosterone hormone was in agreement with that illustrated in ref [86], as it has been reported that serum testosterone level tended to decrease without statistically significant difference between the control (mean 5.81 ng/ml) and treated (mean 5.65-5.66 ng/ml) rats, following 0 weeks treatment with licorice at high dose (1555 mg/Kg) group leading to reduction value of testosterone and did not show any abnormal signs. It was suggested that no observed adverse effect level of licorice extract at 055,1555 and at higher than 1555 mg/kg, the upper limit dose in the repeated dose toxicity protocol recommended in toxicity and that long term exposure to licorice might not cause profound adverse effects [86]. It has been reported that licorice reduce the serum testosterone level and affected androgen metabolism by inhibiting the enzyme β-6 HSD, and 17βHSD hydroxysteroid dehydrogenase or by stimulating aromatase.…”
Section: Resultssupporting
confidence: 93%
“…There are no reports of licorice increasing pregnancy rates [19]; however, licorice extract improved the fertilization capacity of BALB/cA mouse sperm in vitro and fertilized eggs developed normally. In rats, licorice extract increased cyclophosphamide teratogenicity and upregulated the mRNA expression of cytochrome P-450 2B [20], suggesting that licorice root contains multiple components with biological activity that may not necessarily affect gene expression, given that transcription rates are low in spermatozoa [21].…”
Section: Activity Of Crude Licorice Extractmentioning
confidence: 92%
“…Long‐term exposure to water extract of licorice (500, 1000, and 2000 mg/kg, orally, for 9 weeks) showed that NOAEL is higher than 2000 mg/kg. Besides, it had no significant toxicity effects in reproductive organs (Shin et al ., ).…”
Section: Toxicological Findingsmentioning
confidence: 99%